Effects of low-load resistance training with blood flow restriction on muscle size and strength of professional soccer players with muscle imbalance - Denadai, Benedito S. [UNESP]; Oliveira, Felipe B. D. [UNESP]; Camarda, Sergio R. A. [UNESP]; Ribeiro, Leandro [UNESP]; Greco, Camila C. [UNESP] (Int Journal Applied Exercise Physiology, 2017)
The purposes of this study were: 1) to determine whether low intensity resistance training combined with blood flow restriction (LI-BFR) could affect the concentric hamstrings/quadriceps muscle strength ratio (Hcon: Qcon) of professional soccer players with Hcon: Qcon imbalance (Study 1), and; 2) whether hamstrings strength response observed after LI-BFR is associated with muscle hypertrophy (Study 2). In the Study 1, athletes were randomly divided into a training group (n = 6) and a control group (n = 5). In the Study 2, all athletes (n = 11) performed a LI-BFR training program. The athletes participated of a 6-week (twice a week) supervised training program (unilateral knee flexion at 30% 1RM) totalizing 12 training sessions. The concentric peak torque of knee flexors (+ 8%; P < 0.001) and Hcon: Qcon (+ 9%; P < 0.01) were significantly increased after LI-BFR. Moreover, the cross-sectional area (CSA) of the hamstrings was significantly increased (+ 10%; P < 0.001) after LI-BFR. Thus, the addition of hamstrings strength training program using LI-BFR during preseason is able to enhance both Hcon: Qcon and hamstrings CSA of professional soccer players with Hcon: Qcon imbalance.
Keywords: Isokinetic torque; cross sectional area; magnetic resonance imaging; asymmetry